Soft skill elements in structured clinical nursing assessment for undergraduate nursing students: a systematic review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Chong, Mei Chan (Elsevier, 2021)
This systematic review aimed to appraise and synthesize the available evidence that examines the soft skill elements in clinical nursing assessment for undergraduate nursing students. This systematic review also is in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies were identified based on the inclusion criteria with language filters but were limited to articles published from January 2000to March 2019. Tw o reviewers independently conducted the quality assessment, data extraction, and analysis on all included studies. A total of 17 articles were included in this review. Studies showed that without developing adequate soft skill elements in the clinical skill assessment, students are graduating unprepared to be successful in the workplace. There is a need to consider and adopt soft skill elements in clinical skill assessment to improve the quality of nursing graduates and ultimately to create a positive impact on patient outcomes.